PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA FUN THINKERS BOOK TERHADAP HASIL BELAJAR SISWA DAN MOTIVASI BELAJAR SISWA KELAS V SD - Rofikotul Fiqih, Annisa; Ririn Andriani Kumala Dewi; Khoimatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses a true experimental design method with a pretest-posttest control group design. The population of this study were all fifth grade students at SD Negeri 1 Bojong Lor. By using sampling techniques, class V B was determined as the experimental class with a total of 22 students and class V A as the control class with a total of 24 students. Research data was collected through written tests and questionnaires.Based on the results of statistical calculations using two independent t tests (Independent Samples Test), tcount was 0.041 and ttable was 2,100. So tcount (0.041)> ttable (2,100), this shows that Ha was accepted and H0 was rejected. Thus, it can be stated that the problem based learning (PBL) model assisted by fun thinkers book media is applied in learning spatial structures and spatial nets in class V students at SD Negeri 1 Bojong Lor. Based on analysis of questionnaire data, it is proven that the application of the problem based learning model can increase student learning motivation in the learning process of spatial structures and spatial nets in class V students at SD Negeri 1 Bojong Lor.